Komunikasi Dalam Manajemen Pada Implementasi Kurikulum Merdeka - Dianto, Aris; Kusen; Sumarto; Valentine, Femalia (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
Curriculum change is one of the efforts aimed at improving the quality of education in Indonesia. This study examines communication in educational management and explores the implications of implementing the